(untitled) (Research, Society and Development, 2021)
The concept of health extrapolates the significance of the absence of disease, as it is related to public policies aimed at understanding development and quality of life of the population. This work aimed at carrying out health promotion actions, raising students’ awareness, interconnecting the fields of education and health, showing the importance of pharmaceutical training for educational performance. The work was carried out through educational activities in health for students (N=320) of a kindergarten, elementary school and in two high schools (N=100) in the city of Seropédica. The work was done through lectures, with previously defined themes, according to the demand explained by the school manager. During all the lectures, the students demonstrated interactive interest to understand and learn more about the subjects taught. The participation signaled by questions and applications to daily life, guaranteed the tonic in the educational construction, corroborating the proposal of practice and multiplication of knowledge acquired. The results observed confirm the need for training the pharmacist as a health educator, explaining the importance in prevention and promotion actions, improving the quality of life of the population through education.